Unconfined compressive strength of coir fiber reinforced clay - San Diego, Annamarie M.
The need for ground modification is more prevalent as the availability of good site conditions decrease. Among the available methods of ground modification, soil reinforcement is emerging as a promising alternative. Fiber reinforcement involves mixing fibers with soil to improve its strength characteristics. Natural fibers have the following advantages over synthetic: affordability, bulk availability, and eco-friendliness. Coir fiber has the greatest tensile strength and slowest rate of biodegradation among natural fibers. To protect coir from moisture-induced degradation, a physical coating such as kerosene can be used. This present study investigates the effect of kerosene-coated coir on strength and stress-strain response of a cohesive soil. Preliminary soil tests were performed and the soil was classified as CH or high-plasticity clay. Water absorption capacity tests revealed that kerosene reduces moisture intake of coir by up to 170%. Reconstituted samples 2 inches in diameter and 4 inches in height were tested for unconfined compressive strength in optimum moisture and dry states. Samples with fiber concentrations ranging from 0% to 2% by dry weight of soil were prepared. Results showed that incorporation of coir improved the strength and stress-strain response of high-plasticity clay. The optimum fiber concentration was found to be at 1.5%, with a 52% increase in compressive strength compared to plain samples. Aside from increasing peak strength, addition of coir also improved the post-peak behavior of the samples. Stress-strain graphs illustrate improved ductility in the coir-reinforced samples tested at optimum moisture condition. Calculating the soil elastic modulus revealed the same trend as with peak compressive strength. At 1.5% fiber content, a 78% increase in elastic modulus was observed. For dry state, only samples without coir and samples with the optimum fiber content were tested. Results of dry state testing show that addition of coir caused a 43% strength gain. However, dry samples exhibited brittle failure and minimal post-peak shear resistance, regardless of fiber content.